Dynamic Modeling of the Microalgae Cultivation Phase for Energy Production in Open Raceway Ponds and Flat Panel Photobioreactors - Marsullo, Matteo; Mian, Alberto; Ensinas, Adriano Viana; Manente, Giovanni; Lazzaretto, Andrea; Marechal, François (Frontiers in Energy Research, 2015)
A dynamic model of microalgae cultivation phase is presented in this work. Two cultivation technologies are taken into account: the open raceway pond and the flat panel photobioreactor. For each technology, the model is able to evaluate the microalgae areal and volumetric productivity and the energy production and consumption. Differently from the most common existing models in literature, which deal with a specific part of the overall cultivation process, the model presented here includes all physical and chemical quantities that mostly affect microalgae growth: the equation of the specific growth rate for the microalgae is influenced by CO2 and nutrients concentration in the water, light intensity, temperature of the water in the reactor and by the microalgae species being considered. All these input parameters can be tuned to obtain reliable predictions. A comparison with experimental data taken from the literature shows that the predictions are consistent, slightly overestimating the productivity in case of closed photobioreactor. The results obtained by the simulation runs are consistent with those found in literature, being the areal productivity for the open raceway pond between 50 and 70 t/(ha*year) in Southern Spain (Sevilla) and Brazil (Petrolina) and between 250 and 350 t/(ha*year) for the flat panel photobioreactor in the same locations.